1998
DOI: 10.1038/sj.onc.1202389
|View full text |Cite
|
Sign up to set email alerts
|

Point mutations causing Bloom's syndrome abolish ATPase and DNA helicase activities of the BLM protein

Abstract: Bloom's syndrome (BS) is a rare human genetic disorder characterized by mutations within the BLM gene whose primary eects are excessive chromosome breakaoge and increased rates of sister chromatide interchange in somatic cells. We report the characterization of a murine protein (mBLM), highly related to the product of the human BLM gene. This protein exhibits an ATPdependent DNA-helicase activity that unwinds DNA in a 3' ± 5' direction. Single aminoacid substitutions found in BS cells, abolish both ATPase and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 22 publications
(39 reference statements)
1
54
0
1
Order By: Relevance
“…Two disease-causing Bloom missense mutations map to Cys 1036 and Cys 1055 , respectively (32,33), among four conserved cysteine residues in the zinc finger motif. In vitro analysis shows that these mutations abolish BLM ATPase and helicase activities (34). In vitro studies of the RecQ core of the Bloom syndrome protein have shown that when three of the four cysteines in the zinc finger motif were mutated, respectively, the resulting mutants were very unstable.…”
Section: Discussionmentioning
confidence: 99%
“…Two disease-causing Bloom missense mutations map to Cys 1036 and Cys 1055 , respectively (32,33), among four conserved cysteine residues in the zinc finger motif. In vitro analysis shows that these mutations abolish BLM ATPase and helicase activities (34). In vitro studies of the RecQ core of the Bloom syndrome protein have shown that when three of the four cysteines in the zinc finger motif were mutated, respectively, the resulting mutants were very unstable.…”
Section: Discussionmentioning
confidence: 99%
“…The structures of E. coli RecQ and human RECQ1 proteins show that the motif 0 is involved in nucleotide binding, and mutagenesis studies have confirmed that this motif is important for core helicase domain function. For example, substitution of the C-terminal Gln with Ala in RECQ5␤ significantly reduces ATPase activity, and the replacement of the same residue with Arg inactivates the ATPase and helicase activity of murine BLM (Bahr et al, 1998;Garcia et al, 2004). The same mutation is also listed among the naturally occurring mutations of BLM associated with Bloom's syndrome (Ellis et al, 1995).…”
Section: The Core Helicase Domainmentioning
confidence: 99%
“…Chester et al (1998) developed a mouse model for the human Bloom's syndrome, and showed that mouse embryos homozygous for a targeted mutation in the murine Bloom's syndrome gene die by embryonic day 13.5, but little is known about function(s) of BLM. It has been shown that recombinant BLM displays an ATP-and Mg2+ dependent 3' ± 5'-DNA helicase activity (Karow et al, 1997) which is required to correct the genomic instability inherent to BS cells (Bahr et al, 1998;Ne et al, 1999). In the RecQ subfamily, phylogenetic analyses have revealed that the BLM protein is most closely related to Schizosaccharomyces pombe Rqh1 and to Saccharomyces cerevisiae Sgs1p (Murray et al, 1997;Kitao et al, 1998).…”
Section: Introductionmentioning
confidence: 99%